2018
DOI: 10.3390/jcm7120496
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Epidemic in Brazil. II. Post-Mortem Analyses of Neonates with Microcephaly, Stillbirths, and Miscarriage

Abstract: Introduction: The recent Zika virus(ZIKV) epidemic in Brazil was characterized by a range of different clinical presentations, particularly microcephaly, Guillain-Barré syndrome, and death. In this context, we determined the causal relationship between fatal microcephaly cases and ZIKV infection. Methods: Twelve fatal cases of neonates, whose mothers were infected with ZIKV during pregnancy, were examined; cases included nine neonatal deaths due to microcephaly, one miscarriage, and two stillbirths. Tissue sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…For the analysis of fetal tissue samples for viral RNA, we started our analysis with the control fetuses and tested 26 fetal and MFI tissues, consisting of tissues most likely to contain viral RNA based on our prior study (11). Next we generated a heatmap and selected a list of 17 tissues consisting of those most likely to be infected and diagnosed the most infections in the control fetuses, with addition of brain regions most likely to have histological lesions in the current study (such as hippocampus), or found to be infected in human fetuses affected by CZS (51). The criteria to define infection were used systematically for both control and antibody-treated group fetuses: a fetus was considered ZIKV infected if at least one tissue had a consistent qRT-PCR signal (3/3 replicates positive for viral RNA); this situation applied to 11 of the 12 control fetuses.…”
Section: Macaque Infection Experimentsmentioning
confidence: 99%
“…For the analysis of fetal tissue samples for viral RNA, we started our analysis with the control fetuses and tested 26 fetal and MFI tissues, consisting of tissues most likely to contain viral RNA based on our prior study (11). Next we generated a heatmap and selected a list of 17 tissues consisting of those most likely to be infected and diagnosed the most infections in the control fetuses, with addition of brain regions most likely to have histological lesions in the current study (such as hippocampus), or found to be infected in human fetuses affected by CZS (51). The criteria to define infection were used systematically for both control and antibody-treated group fetuses: a fetus was considered ZIKV infected if at least one tissue had a consistent qRT-PCR signal (3/3 replicates positive for viral RNA); this situation applied to 11 of the 12 control fetuses.…”
Section: Macaque Infection Experimentsmentioning
confidence: 99%
“…For the analysis of fetal tissue samples for viral RNA, we started our analysis with the control fetuses and tested 26 fetal and maternal-fetalinterface (MFI) tissues, consisting of tissues most likely to contain viral RNA based on our prior study (11). Next we generated a heatmap and selected a list of 17 tissues consisting of those most likely to be infected and diagnosing the most infections in the control fetuses, with addition of brain regions most likely to have histological lesions in the current study (such as hippocampus), or found to be infected in human fetuses affected by CZS (50). The criteria to define infection were used systematically for both control and antibody treated group fetuses: a fetus was considered ZIKV-infected if at least one tissue had a consistent qRT-PCR signal (3/3 replicates positive for viral RNA); this situation applied to 11 of the 12 control fetuses.…”
Section: Isolation and Quantitation Of Viral Rna From Fluids And Tissmentioning
confidence: 99%
“…Such infectious agents include viruses which can negatively impact pregnancy, being linked to miscarriage and other outcomes such as stillbirth and preterm delivery [ 18 , 21 ]. A number of human viruses, including herpes simplex viruses 1 and 2, cytomegalovirus, dengue virus, zika virus, adenovirus, and adeno-associated virus can potentially infect the placenta, the trophoblast, and/or the cytotrophoblasts after viremia or an ascendant infection [ 18 , 22 , 23 , 24 , 25 , 26 , 27 ]. It is known that cytomegalovirus and herpes simplex viruses can cross the placental barrier, thereby resulting in either SA events or severe birth defects, such as microcephaly [ 21 ].…”
Section: Introductionmentioning
confidence: 99%